Indications for Left Atrial Appendage Occlusion in the United States and Associated In-Hospital Outcomes: Results From the NCDR LAAO Registry. Issue 8 (12th August 2022) - Daimee, Usama A.; Wang, Yongfei; Masoudi, Frederick A.; Varosy, Paul D.; Friedman, Daniel J.; Du, Chengan; Koutras, Cristina; Reddy, Vivek Y.; Saw, Jacqueline; Price, Matthew J.; Kusumoto, Fred M.; Curtis, Jeptha P.; et al.
Abstract : Background: The Food and Drug Administration approved left atrial appendage occlusion with the Watchman device for patients who are at increased stroke risk and are suitable for oral anticoagulation but who have an appropriate reason to seek a nondrug alternative. These broad criteria raise the question of their interpretation in clinical practice. There is a lack of studies comprehensively evaluating the indications for Watchman implantation among a large series of patients from contemporary, real-world practice in the United States. Methods: We used the National Cardiovascular Data Registry Left Atrial Appendage Occlusion Registry to identify Watchman procedures performed between 2016 and 2018. We assessed procedural indications for Watchman implantation in the United States and evaluated the association between procedural indications and in-hospital adverse events. Results: A total of 38 314 procedures were included. The mean patient age was 76.1±8.1 years, and 58.9% were men. The mean CHA2 DS2 -VASc score was 4.8±1.5, whereas the mean hypertension, abnormal renal/liver function, stroke, bleeding history or predisposition, labile international normalized ratio, elderly, drugs/alcohol (HAS-BLED) score was 3.0±1.1. Prior stroke or transient ischemic attack was reported in 40.2% and prior bleeding in 70.1%, with gastrointestinal bleeding being most common (41.9%). The most common site-reported procedural indications for Watchman implantation were increased thromboembolic risk (64.8%) and history of major bleed (64.3%), followed by high fall risk (35.5%). Most (71.9%) had ≥2 procedural indications. Patients with high fall risk had increased risk of in-hospital adverse events (adjusted OR, 1.12; P =0.025), but no other differences were found in the risk of in-hospital adverse events by procedural indication. Conclusions: Among patients in the National Cardiovascular Data Registry Left Atrial Appendage Occlusion Registry, the most common procedural indications for Watchman implantation were increased thromboembolic risk, history of major bleed, and high fall risk. A majority of patients had multiple procedural indications. High fall risk conferred a modestly increased risk of in-hospital adverse events.